Aging in the transport on the corrugated ratchet potential - Mazzitello, Karina Irma (2023)
Under rapid undercooling, glass forming liquids freeze in an amorphous state that can equilibrate only on enormously long time-scales, This is the characteristic sign of aging, which has been observed in a wide range of systems. Brownian ratchet is a widely studied system that exhibits many types of anomalous dynamical behavior. We have investigated the possibility of aging in the collective motion of Brownian particles in a periodic ratchet potential with quenched disorder. We find that when a slowly growing fraction of particles are trapped for long time, the collective movement tends to become super-diffusive. The super-diffusive transport weakly breaks the ergodicity and the time to cover the whole phase space become enormously long and reminiscent of aging behavior.